Health Care Disparities in Patients Undergoing Endoscopic Sinus Surgery for Chronic Rhinosinusitis: Differences in Disease Presentation and Access to Care. (July 2019) - Duerson, Wes; Lafer, Marissa; Ahmed, Omar; Bandler, Ilana; Wang, Binhuan; Lieberman, Seth; Lebowitz, Richard
Objectives: Data on health care disparities by socioeconomic status for chronic rhinosinusitis (CRS) are lacking, and the available literature shows mixed results. The aim of this study was to evaluate several indicators of disease complexity in patients with CRS undergoing endoscopic sinus surgery between a private and a public hospital to determine if there are any disparities in the severity of disease presentation or in access to care. Methods: Two hundred patients with CRS who underwent endoscopic sinus surgery from 2015 to 2017 were retrospectively reviewed. Demographics, disease-specific data, and pre- and postoperative management were collected. Results: Public hospital patients (n = 100) were significantly more likely to be non-Caucasian (73.0% vs 25.0%, P < .0001) and to have Medicaid or no insurance (86.0% vs 4.0%, P < .0001). Patients from the public hospital were more likely to have CRS with nasal polyposis (85.0% vs 60.0%, P < .0001) and to have longer wait times for surgery (68 vs 45 days, P < .0001) and were more likely to be lost to follow-up (26.0% vs 16.0%, P = .031). Patients at the public hospital had CRS symptoms 21% longer ( P = .0206), and if a patient carried a diagnosis of asthma, he or she had on average more severe asthma ( P = .0021). Conclusions: This study suggests that patients of lower socioeconomic status had a longer duration of disease prior to surgery, more often had nasal polyposis, and had decreased access to care, as indicated by increased surgical wait times and being lost to follow-up. Acting as a foundation for further investigation, the ultimate intent of this study is to improve care for all patients.